Wie der Mensch sich setzt Die Beisetzung Fichtes in Hölderlins Pindarfragment Die Asyle - Franz, Michael (Revista Eletrônica Estudos Hegelianos, 2021)
The aim of the present essay is to assign a certain consistency to Hölderlin’s Pindar-fragment Die Asyle, by summarizing it and also explaining how one may understand what I call Fichte’s Beisetzung.